WOMEN'S ENLIGHTENMENT MOVEMENT AS THE PHILOSOPHY OF EDUCATION (LATE 19TH - FIRST HALF OF THE 20TH CENTURY) - Olga Khrystenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
In this article, the author distinguished the ideological foundations of enlightenment work of Ukrainian women's organisations (late 19th - first half of the 20th century) and grounded the necessity to implement a special course in educational programs of the humanities. The methodological basis of the study is axiological and competent approaches. The author examined the educational value of the idea of women's Enlightenment movement and determined the positive experience of women's organisations in the formation of the young generation of Ukrainians with a high level of national consciousness, gender culture and culture of international relations. Using the methods of content analysis, comparative analysis, historical and structural analysis, induction and deduction the author defined the concept of Ukrainian women's Enlightenment movement, as also determined the purposes and suggested the content design of a training course on this social and cultural phenomenon for teacher training colleges in Ukraine.